L’onda lunga dell’Idea di Artisticità (Materiali di Estetica. Terza serie, 2020)
In the aesthetic production of Dino Formaggio there are no pages explicitly dedicated to cinema. However, his “idea of artisticity” allows very useful indications to understand its characteristics and possibilities. It reinforces the opposition to any hypothesis of realism as passive reproduction; the underlying ambiguity of the image, of each image, leads in another direction. Even more so, the many pages dedicated to the circulation of languages can closely concern some obligatory passages concerning the filmic form: the body as expressiveness, the technique as constitutive moment. The idea of modernity as a self-reflection of art is finally manifested in many cinematographic works, especially in recent decades.
Keywords: Dino Formaggio; Artisticity; Cinema